Survey dan Pemetaan Status Hara-P di Kecamatan Kabanjahe Kabupaten Karo - Rino Ginting S; Mukhlis Mukhlis; Gantar Sitanggang (Jurnal Agroekoteknologi, 2015)
The research of survey and mapping nutriens status of P2O5 at Kabanjahe sub-district, regensi Karo, aims to determine the spread of the availability of P2O5 in agricultural areas for plants. The survey was conducted using a free grid survey methode with with density 6.25 ha each of the grid and analysis of P2O5 content of 25% HCl extract. Analysis of the levels of P2O5 done in the laboratory of Research and Technology of the North Sumatra University, Medan. The results showed that the P2O5 classified into 5 criteria such as; very low 18.74 ha, 10 ha Low, Medium 70 ha, 140 ha of high and very high 343.75 ha. From the results obtained by laboratory analysis of soil samples with the highest P2O5 content is 2,376 % and lowest content is 0,016 %.Key words: survey, P status, mapping P2O5